First prosecution of a Dutch doctor since the Euthanasia Act of 2002: what does the verdict mean? - Asscher, Eva Constance Alida (Journal of medical ethics, 2020)
On 11 September 2019, the verdict was read in the first prosecution of a doctor for euthanasia since the Termination of Life on Request and Assisted Suicide (Review Procedures) Act of 2002 was installed in the Netherlands. The case concerned euthanasia on the basis of an advance euthanasia directive (AED) for a patient with severe dementia. In this paper we describe the review process for euthanasia cases in the Netherlands. Then we describe the case in detail, the judgement of the Regional Review Committees for Termination of Life on Request and Euthanasia (RTE) and the judgement of the medical disciplinary court. Both the review committees and the disciplinary court came to the conclusion there were concerns with this case, which mainly hinged on the wording of the AED. They also addressed the lack of communication with the patient, the absence of oral confirmation of the wish to die and the fact that the euthanasia was performed without the patient being aware of this. However, the doctor was acquitted by the criminal court as the court found she had in fact met all due care criteria laid down in the act. We then describe what this judgement means for euthanasia in the Netherlands. It clarifies the power and reach of AEDs, it allows taking conversations with physicians and the testimony of the family into account when interpreting the AED. However, as a practical consequence the prosecution of this physician has led to fear among doctors about prosecution after euthanasia.